The Use of Card Sort to Improve Students’ Vocabulary at MTsN Parepare - Selvy Afrianty (LETS: Journal of Linguistics and English Teaching Studies, 2022)
This research aimed to know by using Card Sort can improve students’ vocabulary at students ofMTsN Parepare. Generally the use of media as teaching aid mainly aimed at increasing the teachingprocess to be more motivating and interesting. This research was conducted in MTsN Parepare.Researcher used quantitative study in the form of Pre – Experimental design with one group pre-testand post-test. There are independent variable and dependent variable. Random sampling is thetechnique to take the sample and VIII.5 is the samples which consist with 26 students. Theinstrument that used is test, observation and documentation. The result calculation of mean scorepre-test of students was 52.31 and mean score post- test of students was 65.57. The result of thisresearch showed there was significant different in statistical analysis where the statistical t-test (2.7)was higher than t-table (1,708) with degree freedom (df = N-1) 25. The researcher concluded the using of Card Sort is able to improve students’ vocabulary. From 15 questionnaires, thestudents answered very positive. Based on the Likert scale, the students were very positive inlearning English by using Card Sort. It means that the Card Sort media makes students have positiveresponse toward in learning vocabulary. The cumulative percentage on the fifteen items of the positive statements questionnaire was 96,62, while the cumulative score that they got from thequestionnaire was 1633. The researcher concluded the using of Card Sort is able to improve students’vocabulary at MTsN Parepare.